1996
DOI: 10.1121/1.414727
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation of an unbaffled vibrating plate with general elastic boundary conditions

Abstract: If the simulations of the radiated field of a baffled plane structure has been deeply studied, the unbaffled case, although more realistic, has retained little attention. The proposed work investigates the radiation, in light fluid, of a plane unbaffled thin structure of finite dimensions and general elastic boundary conditions. The approach used is based on a variational formulation for the plate’s displacement and the pressure jump through the structure. A Rayleigh–Ritz approximation with a polynomial set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…The core idea is to establish a coupling between the free vibration response of the structures and the acoustic medium more accurately. Atalla et al (1996) studied the acoustic radiation from un-baffled thin flat isotropic structures using Rayleigh-Ritz approximation for acoustic parameters and compared the results to the baffled case. A modal superposition technique has been utilised for the computation of coupled structure and acoustic modes by Tournour and Atalla (1998) including a novel integration scheme proposed for handling the singularities of Green's function.…”
Section: Introductionmentioning
confidence: 99%
“…The core idea is to establish a coupling between the free vibration response of the structures and the acoustic medium more accurately. Atalla et al (1996) studied the acoustic radiation from un-baffled thin flat isotropic structures using Rayleigh-Ritz approximation for acoustic parameters and compared the results to the baffled case. A modal superposition technique has been utilised for the computation of coupled structure and acoustic modes by Tournour and Atalla (1998) including a novel integration scheme proposed for handling the singularities of Green's function.…”
Section: Introductionmentioning
confidence: 99%
“…Atalla et al [30] gave a numerical solution for the sound radiation of an unbaffled plate with general boundary conditions. The Kirchhoff-Helmholtz equation allows the pressure to be defined anywhere within the volume enclosing the plate.…”
Section: Unbaffled Plate Modelsmentioning
confidence: 99%
“…From the existing methods, particularly in [29] and [33], the results presented were only focused on single modes. The radiation efficiency due to vibration in multiple modes was calculated in [30,33,34] but only up to relatively low frequency. However, this is not still adequate to give a thorough analysis, particularly to provide a complete investigation into the difference between the radiation from the baffled and unbaffled plate.…”
Section: Unbaffled Plate Modelsmentioning
confidence: 99%
“…Clearly, having a velocity field equal to zero everywhere, apart from the plate surface, makes the problem easier to solve, but this is not always fully representative of a real structure. For this reason, the problem of an unbaffled plate has also been investigated by some authors ( [16], [19] and [21][22][23][24]). Some semi-analytical methods have been proposed and the effect of boundary conditions on unbaffled plates has also been addressed ( [16] and [23]).…”
mentioning
confidence: 99%
“…For this reason, the problem of an unbaffled plate has also been investigated by some authors ( [16], [19] and [21][22][23][24]). Some semi-analytical methods have been proposed and the effect of boundary conditions on unbaffled plates has also been addressed ( [16] and [23]). In particular, results shown in [16] have shown that, in adopting simply supported and/or guided boundary conditions, the variability in radiation efficiency of an unbaffled plate is much lower than the corresponding baffled plate.…”
mentioning
confidence: 99%